Verticillium dahliae Secretes Small RNA to Target Host MIR157d and Retard Plant Floral Transition During Infection - Zhang, Bo-Sen; Li, Ying-Chao; Guo, Hui-Shan; Zhao, Jian-Hua (Frontiers in Plant Science, 2022)
Bidirectional trans-kingdom RNA silencing (or RNA interference, RNAi) plays a key role in plant-pathogen interactions. It has been shown that plant hosts export specific endogenous miRNAs into pathogens to inhibit their virulence, whereas pathogens deliver small RNAs (sRNAs) into plant cells to disturb host immunity. Here, we report a trans-kingdom fungal sRNA retarding host plant floral transition by targeting a miRNA precursor. From Arabidopsis plants infected with Verticillium dahliae, a soil-borne hemibiotrophic pathogenic fungus that causes wilt diseases in a wide range of plant hosts, we obtained a number of possible trans-kingdom V. dahliae sRNAs (VdsRNAs) by sequencing AGO1-immunoprecipitated sRNAs. Among these, a 24-nt VdsRNA derived from V. dahliae rRNA, VdrsR-1, was shown to be an actual trans-kingdom VdsRNA that targets the miR157d precursor MIR157d, resulting in increased rather than reduced miR157d accumulation in V. dahliae-infected plants. Consistent with the miR157 family in the regulation of vegetative and floral transitions by targeting SPL genes in several plant species, we detected two SPL genes, SPL13A/B, that were notably reduced in V. dahliae-infected and VdrsR-1-expressing plants compared with control plants. Furthermore, V. dahliae-infected and VdrsR-1-expressing plants also displayed delayed vegetative phase change and floral transition compared to control plants. Taken together, we disclosed a novel mode of action for a trans-kingdom fungal sRNA, VdrsR-1, which was secreted into host cells to modulate plant floral transition by employing the miR157d/SPL13A/B regulatory module, leading to prolonged host vegetative growth that would undoubtedly benefit fungal propagation.